Evaluation of individual technical-tactical capacity for basketball in the Secondary Education context - D. Cárdenas; E. Moreno (Asociación Española de Ciencias del Deporte, 2010)
Although the methodological focus of the teaching of team sports has had positive modifications, the evaluation phase of the capacity for playing has still not been adequately treated. Most professionals integrate into their teaching programme a percentage of time dedication to the improvement of the individual tactics capacity, its assement, however, being purely technical. Basically, the reason is in the difficulty of formulating objectives tests of this capacity. On the other hand, the teaching of team sports at secondary schools is influenced by problems arising from the lack of equipment, as well as the conditions of practice (number of pupils etc). In this study the results of research in the classroom itself are presented, in which we offer alternative methodologies to solve problems ussually found in secondary schools, such as lack of equipment, too many pupils for the practice, etc. by using the organisations of subgroups (circuit organisation), and further, to desing a measuring instrument for the individual technical-tactical capacity for sport of basketball. The sample was made up of 3 groups of 24 pupils of the 3rd year of the bachillaurate (approximately 17 years of age) who had had no systematic experience of basketball. The results show a considerable improvement in their motor skills and a high degree of satisfaction by the pupils for the task. KEY WORDS: Evaluation, individual tactics, circuit, secondary school teaching.